2017
DOI: 10.11648/j.ajns.20170601.17
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Role Stress and Work Engagement Among Nurses in a Selected Hospital in Cairo

Abstract: Abstract:Health care professionals, with particular regard to nurses, are exposed to several role stressors and demands of workplace that can adversely decrease their work engagement. Work engagement is perceived to inversely correlate with organizational role stress (ORS). The study aimed to investigate the relationship between organizational role stress and work engagement among nurses. A correlational comparative design was utilized in this study. The present study was conducted in all medical units and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Similar results were reported from a study among nurses in a Cairo hospital, where staff nurses scored higher on work engagement than head nurses (Seada, 2017) and from a South African study where auxiliary/assistant nurses also scored higher on work engagement than professional nurses (D'Emiljo & Du Preez, 2017). We also found that respondents who considered leaving nursing scored lower on work engagement than those who had not considered leaving the profession.…”
Section: Work Engagementsupporting
confidence: 88%
“…Similar results were reported from a study among nurses in a Cairo hospital, where staff nurses scored higher on work engagement than head nurses (Seada, 2017) and from a South African study where auxiliary/assistant nurses also scored higher on work engagement than professional nurses (D'Emiljo & Du Preez, 2017). We also found that respondents who considered leaving nursing scored lower on work engagement than those who had not considered leaving the profession.…”
Section: Work Engagementsupporting
confidence: 88%
“…In addition, psychological or physical abuse, an extremely demanding job, a lack of staff members, a high patient frequency, the ensuing excessive burden, and infection exposure are additional causes that frequently cause nurses to stress [40]. Similarly, Arbabisarjou et al, (2017) and Seada (2017) reported that more than three-quarters of the studied nurses had a moderate stress level in their work [38,41].…”
Section: Discussionmentioning
confidence: 94%
“…When nurses suffer psychological distress, their work turnover and administrative leave rates increase, which may cause medical mistakes and problems with patient interaction [37]. Among healthcare professionals, nurses face the most significant levels of occupational stress and are particularly vulnerable to various stressors and workplace expectations that may harm their level of involvement at work [38]. This study aimed to determine if nurses' work stress mediated the link between organizational dehumanization and job engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, work engagement can be defined as "a positive, fulfilling, work-related mental state exhibited by an individual who is committed to delivering outstanding work and is represented by vigor, dedication, and absorption Kim et al, 2019;Niswatey, 2022;Seada, 2017). Whereas, vigor refers to the capacity for facing challenges at work and consistently put effort into one's task through energy and mental resilience (Schaufeli, 2017).…”
Section: Work Engagementmentioning
confidence: 99%